FRI0192 Is early neutropenia associated with clinical response in patients receiving tocilizumab in rheumatoid arthritis?. (23rd January 2014) - Kostine, M.; Barnetche, T.; Ardouin, E.; Joly, M.; Rabois, E.; Glace, B.; Schaeverbeke, T.; Richez, C.
Abstract : Background: A reduction in peripheral blood neutrophils count is usually observed with the anti-interleukin (IL) 6 receptor antibody tocilizumab. This often appears few days after first administration, but mechanisms are not completely established. Objectives: To evaluate the evolution of neutrophils count under tocilizumab (anti IL-6R) treatment for rheumatoid arthritis affected patients and to correlate this evolution with clinical response. Methods: We performed a multicentric retrospective study including patients with RA treated by tocilizumab +/– DMARDs in 4 University French Centers (Bordeaux, Clermont-Ferrand, Limoges and Montpellier). Neutrophils, inflammatory parameters and DAS28 (ESR) were recorded at baseline, and after one and three months of treatment. The comparisons were performed using Student's t-test or Mann-Whitney test when appropriate. A statistical significant p-value of 0, 05 was selected. Results: 122 patients were included with mean age of 59, 9±12, 6 years-old and a mean disease duration of 13, 2±9, 5 years. The mean DAS28 (ESR) at inclusion was about 5, 25±1, 22, and decreased significantly after one month of treatment to 3, 71±1, 35 (p<10 -4 ), and to 3, 14±1, 32 (p<10 -4 ) after three months of treatment. According to the EULAR response criteria, 2 patients were classified as good responders (1, 6%), 95 as moderate responders (77, 9%) and 25 as non-responders (20, 5%). The neutrophils count shows a significant decrease between the introduction of tocilizumab therapy and after one month of treatment (5815±2514/mm 3 vs. 4085±2433/mm 3, p<10 -4 ), whereas it stays at the same level between the first and the third month of treatment (4014±2428/mm 3 vs. 4225±2342/mm 3, p=0, 27). The frequency of neutropenia (neutrophils≤1500/mm 3 ) was about 0, 8% (1/122) at inclusion, 4, 9% (6/122) after one month and 3, 3% (4/122) after three months of treatment. The neutrophils count decreases significantly between the inclusion and first month of treatment in the subgroup of Month 3 responders (6111±2850/mm 3 vs. 3987±2407, p<10 -4 with Mann-Whitney test), whereas this decrease is not significant in the subgroup of month 3 non-responders (5510±2360/mm 3 vs. 4320±2458/mm 3, p=0, 12 with Mann-Whitney test). The DAS (ESR) difference between Month 0 and Month 3 was positively correlated with the difference of the neutrophils count between Month 0 and Month 1 (p=0, 04; r=0, 19). Conclusions: This study reveals correlation between neutrophils decrease and clinical response during tocilizumab therapy. Accordingly with our previous report showing decrease of myeloid dendritic cells and monocytes during tocilizumab therapy, these new data suggest a specific effect of tocilizumab on cells from myeloid lineage. Disclosure of Interest: None Declared